Existence of positive solutions for certain partial difference equations - Binggen Zhang; Qiuju Xing (Discrete Dynamics in Nature and Society)
We give some sufficient conditions for the existence of positive solutions of partial difference equation aAm+1,n+1+bAm,n+1+cAm+1,n−dAm,n+Pm,nAm−k,n−1=0 by two different methods.